LEXICAL COHESION IN THE NOVEL PERGI BY TERE LIYE - Refni Nadila; Charlina Charlina; Elvrin Septyanti (STKIP PGRI Jombang, 2021)
This research aims to describe the types and meanings that appear in lexical cohesion in the novel Pergi by Tere Liye. The benefits of this research are theoretical and practical benefits. This research uses descriptive qualitative recearch. The data of this research are in the form of words and phrases contained in the novel Pergi by Tere Liye, the source of data in this study is a collection of texts in the novel Pergi by Tere Liye. In this research, the writer uses descriptive method, using documentation technique, namely reading and taking notes. The data analysis technique uses three stages, namely, data reduction, data presentation, and conclusions. The validity of this research data uses triangulation theory. based on the results of the research found, there are as many as 97 lexical cohesion data in the novel Pergi by Tere Liye. The results of the lexical cohesion research data contained in the novel Pergi by Tere Liye include the types of repetitions as many as 55 data, which consists of 12 data epizeukis repetitions, 3 data repetition of tautotes, 14 data of anaphora repetitions, 11 data of epistropha repetition, simploke repetition of 3 data, 9 data for mesodiplosis repetition, 2 data for epanalepsis repetition, and 1 data for anadiplosis repetition. Then the type of synonymous lexical cohesion is 6 data, antonym is 18 data, collocation is 6 data, hyponym is 5 data, and finally equivalence 7 data.Key words: lexical cohesion, novel Pergi, Tere Liye